Corruption As a Threat to Economic Security: History And Modernity - Viktoria TSIKLAURI1; Pavel KLIMENKO1; Ivan AFANASEV2; Yulia BRUSENTSEVA1; Alina EVLOEVA1 (Communications of International Proceedings, 2021)
Corrupt crime, like other types of crime, is distinguished on the basis of not a formal, but a substantive criterion that determines the specificity of the phenomenon, determines the peculiarity of the mechanism of criminal behavior, the system of its determination and the specificity of the response. The mechanism of corruption forms the difference between real and declared values ​​and presupposes “double consciousness”. As a result, state relations and information flows are distorted. Corruption as a socio-economic phenomenon poses a threat to national security, infringing on the vital interests of the individual, society and the state as a whole. Corruption processes affect all spheres of public life, including economic security. Economic security is the basis (foundation) of the national security system of every sovereign state, and corruption and the shadow economy are the basis for the criminalization of economic relations. At present, in the context of general globalization, it is becoming very obvious that corruption, like crime in general, throughout the history of human development is trying to thoroughly infiltrate public life. Such actions ultimately lead to a violation of the principles of social justice, and also impedes the successful and dynamic development of each state. Corruption has become one of the main problems of the 21st century for the entire civilized world, and already bears an international character. The purpose of the study is to reveal the complexity of the problem of the prevalence of corruption in modern Russia and to contribute to the development of certain aspects of the problem of the formation of a mechanism for combating corruption. In the process of solving research problems, general scientific methods of cognition were used: analysis, synthesis, comparison, analogy, deduction, induction, abstraction. As well as private scientific and special methods - comparative legal, formal legal, etc. The methodological basis of the study was formed by the principles of theoretical and legal analysis used in the process of studying the essence, content and features of the formation of the Russian legal order in the field of combating corruption, identifying contradictions in functioning, and development of proposals for its improvement.
Keywords: Corruption; Crime; Corruption Perception Index; Countermeasures.